Respostas

2014-07-16T14:35:23-03:00
1(2X-5)=0                          1(3X-2)=0
X=1                                   X=1
X=5                                   X=2
    2                                       3
  • Usuário do Brainly
2014-07-16T15:05:21-03:00
{y = 2x - 5
{y = 3x - 2

{- 2x + y = - 5 . (- 3)
{- 3x + y = - 2 . (2)

{6x - 3y = 15
{- 6x + 2y = - 4

- y = 11 . (- 1)
y = - 11

- 2x + y = - 5
- 2x + (- 11) = - 5
- 2x - 11 = - 5
- 2x = - 5 + 11
- 2x = 6 . (- 1)
2x = - 6
x = - 6/2
x = - 3

I(x, y)
I(- 3, - 11)